Pengaruh Kombinasi Giberelin (GA3) dan Air Kelapa Muda terhadap Pertumbuhan Mata Tunas Tanaman Jeruk Siam (Citrus nobilis L.) Hasil Okulasi - Warda Ningsih; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to determine the effect of the combination of GA3 and young coconut water and to get the best treatment on the growth of occulationorange. The research was conducted at the Experimental Garden of the Faculty of Agriculture, University of Riau, from June to October 2019. The study used a completely randomized design (CRD), consisting of concentrations of growth regulators (Z), namely: Z1 = application ofGA33%, Z2 = application of coconut water young 75%, Z3 = combinationGA3 2% and young coconut water 25%, Z4 = combinationGA3 2% and young coconut water 50%, Z5 = combinationGA31% and young coconut water 25%, Z6 = combination GA3 1% and 50% young coconut water, consisting of 4 replications. Parameters observed were shoot emergence, number of branches, length of branches, increase in rootstock diameter, number of leaves and branch dry weight. The results showed that the combination of GA3 2% and 50% young coconut water showed the fastest shoot emergence time was 25.75 days, increasing the number of leaves namely 21.50 strands and branch dry weight of 1.65 grams. The combination of GA3 1% and 50% young coconut water showed better results in increasing the length of the branches and the dry weight of the branches.Keywords: gibberellin, young coconut water, oranges and budding.